Cellular Localization of Exogenous Cry1Ab/c and its Interaction with Plasma Membrane Ca2+-ATPase in Transgenic Rice - Fu, Jianmei; Shi, Yu; Liu, Laipan; Liu, Biao (Frontiers in Bioengineering and Biotechnology, 2021)
The cellular localization of exogenous proteins expressed in transgenic crops not only determines their stability (Rawat et al., 2011), but also their effects on crop growth and development, including under stressful conditions; however, the underlying molecular mechanisms remain unknown. Here, we determined the cellular distribution of exogenously expressed Cry1Ab/c protein in insect-resistant transgenic rice Huahui-1 (HH1) cells through subcellular localization, immunohistochemistry, immunofluorescence, and western blot analyses. Interaction between the Cry1Ab/c protein and the preliminarily screened endogenous plasma membrane protein Ca2+-ATPase was investigated through yeast two-hybrid, bimolecular fluorescence complementation (BIFC), and co-immunoprecipitation analyses. The potential interaction mechanism was analyzed by comparing the cellular localization and interaction sites between Cry1Ab/c and Ca2+-ATPase. Phenotypic indices and Ca2+-ATPase activity, which may be regulated by the Cry1Ab/c–Ca2+-ATPase interaction, were determined in transgenic HH1 and the parental line Minghui-63 under stress-free and salt-stress conditions. The results showed that Cry1Ab/c was not only distributed in the cytoplasm and nucleus but was also distributed on the plasma membrane, where it interacted with plasma membrane Ca2+-ATPase. This interaction partially retain plasma membrane protein Ca2+-ATPase in the nucleus by a BIFC experiment and thus may affect Ca2+-ATPase activity on the membrane by altering the cellular location of the protein. Consistently, our results confirmed that the presence of Cry1Ab/c in the transgenic HH1 resulted in a reduction in Ca2+-ATPase activity as well as causing detrimental effects on plant phenotype, including significantly reduced plant height and biomass, compared to parental MH63; and that these detrimental effects were more pronounced under salt stress conditions, impacting the salt resistance of the transgenic plants. We suggest that the Cry1Ab/c–Ca2+-ATPase interaction may explain the plasma membrane localization of Cry1Ab/c, which lacks a signal peptide and a transmembrane domain, and the adverse effects of Cry1Ab/c expression on the growth and development of transgenic HH1 plants under salt stress. This information may clarify the molecular mechanisms of these unintended effects and demonstrate the feasibility of evaluating the success and performance of genetic modification of commercially vital crops.